The comparison of the effects of dexmedetomidine, fentanyl and esmolol on prevention of hemodynamic response to intubation - Gogus,Nermin (2014)
Background and objectives:Laryngoscopy and intubation can cause hemodynamic response. Various medications may be employed to control that response. In this study, we aimed to compare the effects of dexmedetomidine, fentanyl and esmolol on hemodynamic response.Methods:Ninety elective surgery patients who needed endotracheal intubation who were in American Society of Anesthesiology I–II group and ages between 21 and 65 years were included in that prospective, randomized, double-blind study. Systolic, diastolic, mean arterial pressures, heart rates at the time of admittance at operation room were recorded as basal measurements. The patients were randomized into three groups: Group I (n = 30) received 1 μg/kg dexmedetomidine with infusion in 10 min, Group II (n = 30) received 2 μg/kg fentanyl, Group III received 2 mg/kg esmolol 2 min before induction. The patients were intubated in 3 min. Systolic, diastolic, mean arterial pressures and heart rates were measured before induction, before intubation and 1, 3, 5, 10 min after intubation.Results:When basal levels were compared with the measurements of the groups, it was found that 5 and 10 min after intubation heart rate in Group I and systolic, diastolic, mean arterial pressures in Group III were lower than other measurements (p < 0.05).Conclusions:Dexmedetomidine was superior in the prevention of tachycardia. Esmolol prevented sytolic, diastolic, mean arterial pressure increases following intubation. We concluded that further studies are needed in order to find a strategy that prevents the increase in systemic blood pressure and heart rate both.